Assessing Technology and Livelihood Education Skills and Academic Performance of Elementary Pupils in Digos City - Berido, Meriam; Almerez, Queenie Lyn; Trinidad, Amelie; Condes, Rikka Bianca; Noel, Helen (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to investigate the significant relationship between Technology and Livelihood Education skills and the performance of elementary pupils, providing a basis for an intervention program. A non-experimental, quantitative research design employing a descriptive correlational approach was used in the study, which involved 324 public elementary grade six pupils in the Digos Oriental district, Digos City, Philippines. The primary data source for this study was a teacher-made or self-designed instrument and a validated survey questionnaire. The study found that the overall respondents’ level of skills was a mean score of 2.71, described as proficient or average, across the areas of Technology and Livelihood Education, including Agri-Fishery Arts, Home Economics, Industrial Arts, Entrepreneurship, and ICT. Furthermore, the pupils’ TLE skills suggested that the study sample was primarily composed of different statements, but with corresponding means and descriptive levels. In terms of TLE pupils’ level of skills, the results revealed that both Agri-Fishery Arts and Home Economics achieved the same mean score of 2.76, ranking them in the highest category. However, there were some pupils ' skills/competencies in Home Economics, Industrial Arts, and ICT who did not meet the standard requirements of the industries for future employment. In addition, pupils’ TLE performance was rated at a very satisfactory level in the specified areas of TLE. Furthermore, no significant correlation was found between TLE skills and the performance of elementary pupils; therefore, administrators may address the diverse population of grade six pupils by revising the curriculum and proposing further enhancements to the training or intervention program. TLE teachers can continually improve the systems and procedures in delivering their instruction and consider additional intervention programs or goal-oriented actions through integrative and collaborative activities as part of the competency or skills management program.